The Saami Peoples from the Time of the Voyage of Ottar to Thomas von Westen - Meriot, Christian (ARCTIC, 1984)
The history of the discovery and understanding of the Saami peoples can be divided into three periods. The earliest record goes back to Tacitus . This prehistory of the Sammi peoples can be said to end with the History of the Langobards by Paulus Diaconus (Varnefrid) about A.D. 780 . The latest period of discovery began in the eighteenth century, through scholars in various disciplines, and through countless travellers passing through more for recreation than for reasons of serious exploration. Between these two phases, there was a long transition period beginning with Ottar's account of his journey in Lappland (dated at the end of the ninth century, about 890), and ending at the turn of the seventeenth into the eighteenth century with the first scientific works of learned men such as von Westen (1682-1727). .